Цифровий вимірювач параметрів коливних систем - Проць, Р. В.; Романюк, А. В.; Семянистий, К. С.; Prots, R.; Romaniuk, A.; Semianystyj, K. (Видавництво Львівської політехніки, 2019)
Розглянуто принцип побудови цифрового вимірювача параметрів коливних контурів: добротності, резонансної частоти та смуги пропускання без дослідження резонансної характеристики контура.

The principle of construction of a digital meter of parameters of oscillating circuits is considered in the article. The measurement of the main parameters - Q factor, resonant frequency f0 and bandwidth Δf is carried out without studying the resonant characteristics of the circuit. The principle of measuring the quality factor of the circuit is based on counting the number N of pulses of free oscillations of the oscillating system after its shock excitation. It is shown that the number N of free oscillations of the circuit from the first measurement of the amplitude U1 to the N with the amplitude U2 = 0.0432 U1 corresponds to the value of the Q factor of the oscillating circuit. The block diagram of the digital meter of parameters of oscillating systems and algorithm of its work are resulted. Principle of considered of digital settings meter of oscillating circuit – virtue resonant frequency and band width without exploring of resonance characteristics of the circuit.
Digital measuring parameter of oscillating systems
Keywords: коливна система; добротність; смуга пропускання; oscillating system; virtue; band width; Q factor; 621.317.08